Increased tacrolimus blood concentration by Beni‐Madonna – a new hybrid citrus cultivar categorized as 'Tangor', in a liver transplant patient: likely furanocoumarin‐mediated inhibition of CYP3A4 or P‐glycoprotein. (14th September 2018) - Ushijima, Kentaro; Mizuta, Koichi; Otomo, Shinya; Ogaki, Keiko; Sanada, Yukihiro; Hirata, Yuta; Ihara, Yoshiyuki; Urahashi, Taizen; Imai, Yasushi; Fujimura, Akio
Abstract : Adverse event: A drug interaction leading to greater exposure to tacrolimus. Drug implicated: Tacrolimus and Beni‐Madonna (a new cultivar citrus categorized as 'Tangor'). The patient: A 9‐month‐old girl with biliary atresia (body weight, 7.5 kg) taking tacrolimus after liver transplantation. Evidence that links the drug to the event: The time course was consistent with the appearance of the interaction, which was confirmed by an increase in the blood concentration of tacrolimus. Dihydroxybergamottin was detected in peel of Beni‐Madonna and in peel and fruit pulp of grapefruit. Management: Avoiding Beni‐Madonna intake. Mechanism: Inhibition of activity of CYP3A4, P‐glycoprotein, or both, by Beni‐Madonna. Implication for therapy: Clinicians should be aware of this potential interaction, and patients taking drugs such as tacrolimus (the kinetics of which are affected by grapefruit juice) should avoid Beni‐Madonna intake. Hypothesis to be tested: Further study is required to determine if other Citrus species categorized as Tangor contain furanocoumarins.